The (re)discovery of ectomycorrhizal symbioses in Neotropical ecosystems sketched in Florianópolis - Roy, Mélanie (2017)
The VIIIthBrazilian Mycological Congress, held in Florianopolis(Brazil) in October 2016, was organized by the UniversidadeFederal de Santa Catarina and brought together more than 1000scientists of 20 nationalities, which illustrates the dynamism ofSouth American mycology, in many fields. One of the major take-home messages, amongst many research talks and posters, was therising interest in the ectomycorrhizal (EM) symbiosis, which wasaddressedbybothasymposium anda3-day workshop ?Totherootsof trees: growing awareness of ectomycorrhizal symbioses in theNeotropics?. Talks on this symbiosis were given by taxonomists andecologists, and focused on the Neotropics, the tropical realm thatextends from the central plateau of Mexico and which includesSouth America. The inventories of ectomycorrhizal fungi (EMF),observations of EM roots, and metabarcoding studies presentedrevealed a hitherto unsuspected abundance of the EM symbiosis toall participants, including a number of South-American students.This meeting provided great opportunities to share points of viewon the historical reasons behind gaps in knowledge on EMFassociations in neotropical low-elevation areas. The meeting alsohighlighted recent discoveries and forthcoming challenges, basedon three complementary approaches: studies on fruitbodies, EMroots, and the metabarcoding of soil samples.